Strategi Konten Instagram @dprd.lomboktimur dalam Membangun Transparansi dan Kepercayaan Publik - Yuni Elmina; Iwan Joko Prasetyo; Harliantara Harliantara (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the Instagram content strategy of the @dprd.lomboktimur account in building transparency and public trust in the regional legislative body. Social media has become a strategic tool for government institutions to communicate with the public, but its effectiveness depends heavily on the content strategy implemented. Based on analytical data from Toolzu.com for the 2025-2026 period, the @dprd.lomboktimur Instagram account had 417 followers, 136 posts, an engagement rate of 0.14%, and an average user activity of 1.96%. This study used a descriptive qualitative approach with digital content analysis and a literature review on government communication. The results show that the implemented content strategy still focuses on documenting internal activities (commission meetings, working visits) with the dominant keywords